Desenvolvimento de interface com usuário dirigido por modelos e geração automática de código - Lucas Villela Neder Issa (2006)
UML models are frequently used and are important in software engineering, however, it is normal that after the system codification starts these models tend to lose their importance and become outdated as the development advances. In this work, this problem is treated through the application of MDA techniques (Model Driven Architecture) which aim at software development through the creation of models that are used in the automatic generation of code. Based on the presented work, we propose a method for interface generation (MDGI - Method of Development and Generation of Interfaces) that allows generating models of recurrent patterns in systems. These patterns refer to the user interface and are generated from the domain model of the application. The MDGI follows the MDA philosophy; therefore it is totally compatible with it. As a final result of this work, in addition to the MDGI, a technology and platform independent model for user interaction called PIM UI was created, and can be used in the MDGI execution. A use case was implemented following the proposed method and the result was analyzed comparing with manual development. The results observed in this analysis show that by using MDGI it is possible to increase productivity, in the analised situation. In this analysis, it is also pointed out that the application of MDGI allows better reuse level because it encapsulates knowledge for the transformation from a model into another more detailed model.